Building teacher quality in India : examining policy frameworks and implementation outcomes - Wiseman, Alexander W., 1968-; Kumar, Preeti (International perspectives on education and society ;, 2021)
In an era of educational globalization, teacher quality is heralded as a key factor to improve education quality worldwide. Since the 1980s, global, national, and local education policies and reforms have consistently focused on improving teacher quality in order to improve student learning outcomes. In India, which has one of the largest student populations and fastest growing economies in the world, the quality of teaching is blamed for the poor performance by Indian students on internationally-comparative assessments. As a result, Indian national policy documents and curriculum frameworks have repeatedly called for drastic improvements in teacher preparation and performance, but with few widespread results. By identifying and analyzing various measures of teacher quality, and how teacher quality varies in India, this book provides an evidence-based framework for policymakers to further improve teacher quality in India. Building Teacher Quality in India provides suggestions for further research in order to augment educational practices in India, secure better student achievement, and improve the country's global standing. This book is essential reading for education researchers and policymakers looking at teacher quality as a measure to improve student performance.